Optimization of axially symmetric drift tube geometry - Demchenko, P.O.; Shulika, M.G. (Вопросы атомной науки и техники, 2001)
The integral equation method had been used for calculation of the electric field strength between drift tubes as well as on their surfaces, power distribution of RF surface losses, and mutual tubes capacitance. The method gives an opportunity to find the critical surface points where the field strength and the linear power density have the maximum values.